2010
DOI: 10.2169/internalmedicine.49.4221
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hepatitis due to Hepatitis E Virus Genotype 1 As an Imported Infectious Disease in Japan

Abstract: An 18-year-old Nepalese man was admitted due to general malaise and anorexia a month after coming to Japan. Laboratory tests showed elevation of transaminase and positivity for IgM anti-HEV antibody. Serum HEV RNA was detected by RT-PCR amplifications. An HEV genome phylogenetic tree, constructed using an 821-nucleotide sequence in the open reading frame 1, indicated that the genotype was 1. HEV genotype 1 is epidemic in South Asia, Africa and South America, and the incidence of acute hepatitis due to HEV geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…However, the indication for this therapy remains controversial, with some reports suggesting no improvement in mortality in patients with advanced liver failure ( 15 ). Despite this controversy, several studies have suggested the efficacy of steroid therapy in treating liver damage in acute hepatitis E ( 2 , 16 ). In the present case, due to the patient's rapidly deteriorating liver function and coagulation capacity, we deemed aggressive treatment necessary and initiated steroid therapy at an early stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the indication for this therapy remains controversial, with some reports suggesting no improvement in mortality in patients with advanced liver failure ( 15 ). Despite this controversy, several studies have suggested the efficacy of steroid therapy in treating liver damage in acute hepatitis E ( 2 , 16 ). In the present case, due to the patient's rapidly deteriorating liver function and coagulation capacity, we deemed aggressive treatment necessary and initiated steroid therapy at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…HEV genotype 1 is prevalent in developing regions of Asia, Africa, and South America. In contrast, acute hepatitis E is rare in developed regions, including Japan, where only sporadic cases of HEV genotypes 3 or 4 are found ( 2 ). Most people are asymptomatic or develop flu-like symptoms, such as fatigue, a fever, and nausea, in response to acute HEV infection ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the four major genotypes infecting humans, HEV-1 and genotype 2 HEV (HEV-2) are restricted to humans and have been responsible for multiple outbreaks in developing countries where the virus is transmitted through drinking contaminated water [18]. Although HEV-1 typically affects people in developing countries, such as South Asia and most countries in sub-Saharan Africa [19], imported infections have been reported in industrialized countries, including Japan [20][21][22]. HEV-1 infection in pregnant women frequently leads to infant mortality or premature delivery.…”
Section: Introductionmentioning
confidence: 99%